2014
DOI: 10.1080/09658211.2014.886702
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval and phenomenology of autobiographical memories in blind individuals

Abstract: Although visual imagery is argued to be an essential component of autobiographical memory, there have been surprisingly few studies on autobiographical memory processes in blind individuals, who have had no or limited visual input. The purpose of the present study was to investigate how blindness affects retrieval and phenomenology of autobiographical memories. We asked 48 congenital/early blind and 48 sighted participants to recall autobiographical memories in response to six cue words, and to fill out the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 52 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…The Tekcan and Göz norms provide concreteness and imageability ratings as well as association sets for 600 of the words selected from Göz (2003). These norms have been widely used by researchers using Turkish materials (e.g., Booth, 2014;Booth, Mackintosh, Mobini, Oztop, & Nunn, 2014;Ilgaz, Altun, & Aşkar, 2014;Tekcan et al, 2015). In addition to these norms, a few databases are more frequently used in linguistics research, such as the Turkish National Corpus (Aksan et al, 2012) and Turkish Electronic Living Lexicon (Inkelas, Küntay, Orgun, & Sprouse, 2000).…”
Section: Aoa Norms In Turkishmentioning
confidence: 99%
“…The Tekcan and Göz norms provide concreteness and imageability ratings as well as association sets for 600 of the words selected from Göz (2003). These norms have been widely used by researchers using Turkish materials (e.g., Booth, 2014;Booth, Mackintosh, Mobini, Oztop, & Nunn, 2014;Ilgaz, Altun, & Aşkar, 2014;Tekcan et al, 2015). In addition to these norms, a few databases are more frequently used in linguistics research, such as the Turkish National Corpus (Aksan et al, 2012) and Turkish Electronic Living Lexicon (Inkelas, Küntay, Orgun, & Sprouse, 2000).…”
Section: Aoa Norms In Turkishmentioning
confidence: 99%
“…In addition, neuroimaging studies have shown activation of visual brain areas during autobiographical recall (e.g., Viard et al, 2007; for a review, see, Piolino, Desgranges, & Eustache, 2009). Moreover, there is evidence of low autobiographical recall in blind individuals (Tekcan et al, 2014). These findings suggest visual processing as a core component of phenomenological reliving during autobiographical recall.…”
Section: Discussionmentioning
confidence: 99%
“…earliest childhood memory, very vivid memory). A recent study adopted this approach to examine autobiographical memory qualities of blind participants (Tekcan et al, 2015). To some extent, this is the complementary approach to our own.…”
Section: Introductionmentioning
confidence: 99%